2019
DOI: 10.3390/ani9080532
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness Expressions of Bitter Taste Receptors Against Denatonium Benzoate and Genistein in the Heart, Spleen, Lung, Kidney, and Bursa Fabricius of Chinese Fast Yellow Chicken

Abstract: The present study was conducted to investigate the responsiveness expressions of ggTas2Rs against denatonium benzoate (DB) and genistein (GEN) in several organs of the Chinese Fast Yellow Chicken. A total of 300 one-day-old chicks that weighed an average of 32 g were randomly allocated into five groups with five replicates for 56 consecutive days. The dietary treatments consisted of basal diet, denatonium benzoate (5 mg/kg, 20 mg/kg, and 100 mg/kg), and genistein 25 mg/kg. The results of qRT-PCR indicated sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Interestingly, dietary preferences are suppressed when the tongue becomes paralyzed, suggesting the role of olfaction in dietary fat preferences [56]. Meanwhile, T2Rs have been identified in nonoral tissues, including the respiratory tract, the gut, the spleen, the lung, the heart, and bursa Fabricius, suggesting its involvement in other physiological functions such as appetite regulation, innate immunity, and internal organs, besides taste [57, 58]. In addition, preferences for a balanced diet containing synthetic AA (potentially related to umami taste) suggest that lysine, methionine, and tryptophan in a diet increase feed intake [59].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, dietary preferences are suppressed when the tongue becomes paralyzed, suggesting the role of olfaction in dietary fat preferences [56]. Meanwhile, T2Rs have been identified in nonoral tissues, including the respiratory tract, the gut, the spleen, the lung, the heart, and bursa Fabricius, suggesting its involvement in other physiological functions such as appetite regulation, innate immunity, and internal organs, besides taste [57, 58]. In addition, preferences for a balanced diet containing synthetic AA (potentially related to umami taste) suggest that lysine, methionine, and tryptophan in a diet increase feed intake [59].…”
Section: Discussionmentioning
confidence: 99%
“…Fast yellow chicken [ 75 ] was used to evaluate the efficacy of the stimulants on the individual level on a chicken farm. All chickens were from the Guangdong Huanong Zhengda Poultry Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%
“…7 days) causes a decrease in the expression of apoptosis and autophagy-related genes—caspase (Casp) 2, Casp3, Casp7, Casp9, Bcl-2l1 (B cell lymphoma 2 like 1), Mcl (mantle cell lymphoma), Bid (BH3-interacting domain death agonist), and Noxa (NADPH oxidase activator), along with increased expression of antioxidant enzymes or mediators such as glutathione peroxidase 1 (Gpx1), catalase (CAT), superoxide dismutase 1 (SOD1) and calpain-1 in whole heart tissues of experimental animals (Hamdard et al 2019b ). However, at higher doses and chronic treatment with denatonium benzoate, Hamdard et al ( 2019a , b ) demonstrated increased expression of the apoptosis and autophagy-related genes, suggesting that TAS2R activation may be beneficial at low doses and acute treatment period (Hamdard et al 2019b ).…”
Section: Bitter Taste Receptors Of the Heart And Their Signal Transdu...mentioning
confidence: 99%